First record of Tigrisoma fasciatum (Such, 1825) (Aves: Ardeidae) in the State of Amapá, Brazil and updated species distribution in Central and South America - Kajiki, Lia Nahomi; Togura, Cintia Massumi; Michalski, Fernanda (Biota Neotropica, 2013)
The Fasciated Tiger-heron (Tigrisoma fasciatum) is considered endangered in Brazil and Argentina. Although this species has a large range in Central and South America, its records are scattered and scarce. We used a combination of searches in the scientific literature and new field records to provide an updated distributional range of this species. Searches for records and photos of T. fasciatum were conducted using online databases. We also conducted field surveys along the margins of the Araguari and Falsino rivers, in the National Forest of Amapá, a sustainable protected area in the eastern Brazilian Amazon. Our literature review provided a total of 25 new distributional records of T. fasciatum. During our river based surveys we recorded one individual of T. fasciatum, which represents an extension of 499 km from the nearest previously documented occurrence. We present these findings in an up to date distributional map of T. fasciatum and highlight the need of further studies in order to better understand the species distribution and ecology.